2009
DOI: 10.1038/npp.2009.218
|View full text |Cite
|
Sign up to set email alerts
|

Familial Risk for Mood Disorder and the Personality Risk Factor, Neuroticism, Interact in Their Association with Frontolimbic Serotonin 2A Receptor Binding

Abstract: Life stress is a robust risk factor for later development of mood disorders, particularly for individuals at familial risk. Likewise, scoring high on the personality trait neuroticism is associated with an increased risk for mood disorders. Neuroticism partly reflects stress vulnerability and is positively correlated to frontolimbic serotonin 2A (5-HT 2A ) receptor binding. Here, we investigate whether neuroticism interacts with familial risk in relation to frontolimbic 5-HT 2A receptor binding. Twenty-one hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 53 publications
2
44
0
Order By: Relevance
“…Increased cortical binding to the serotonin-2A receptor has been reported in some small sample studies of postmenopausal women following replacement hormone therapy (Moses et al, 2000; Kugaya et al, 2003), though not in other studies of hormonal contraception or replacement therapy (Frokjaer et al, 2008). A positive correlation between cortical serotonin-2A receptor binding and plasma estradiol levels has been reported in healthy men, with no independent effects for testosterone (Frokjaer et al, 2010). Future studies should sample sex hormones at the time of PET study to control for this variable.…”
Section: Discussionmentioning
confidence: 98%
“…Increased cortical binding to the serotonin-2A receptor has been reported in some small sample studies of postmenopausal women following replacement hormone therapy (Moses et al, 2000; Kugaya et al, 2003), though not in other studies of hormonal contraception or replacement therapy (Frokjaer et al, 2008). A positive correlation between cortical serotonin-2A receptor binding and plasma estradiol levels has been reported in healthy men, with no independent effects for testosterone (Frokjaer et al, 2010). Future studies should sample sex hormones at the time of PET study to control for this variable.…”
Section: Discussionmentioning
confidence: 98%
“…For example, previous studies have found that NA may enhance drug craving and the likelihood of drug abuse through increased noradrenergic and dopaminergic activity in cortical and subcortical mesolimbic areas. 48,71,72 Interestingly, NA has also been found to be associated with decreased central serotonergic (5-HT) activity, 1,29,31,32,41 one of the main neurotransmitter systems involved in the regulation of craving and drug use. In previous studies, decreased 5-HT activity has been found to be associated with enhanced self-reports of craving and with an increased likelihood of drug abuse in patients with various forms of drug problem.…”
Section: 0 Discussionmentioning
confidence: 99%
“…Self-reported NEO Personality Inventory-Revised personality trait scores were filled in online at baseline to derive the neuroticism score. Neuroticism was considered relevant, since it is a robust risk factor for developing major depression that might interact with other risk factors in the interplay with markers of serotonin signaling as seen previously (33). Side effects typical to GnRHa were scored by telephone interview at days 7, 12, and 30 postintervention and the day of bleeding was registered.…”
Section: Baselinementioning
confidence: 99%